The Effects on Turkish Ice Cream Employees' Musculoskeletal Pain of Physical Activity and Ergonomy Programme in Workplace - (:unkn) unknown (My University, 2021)
ABSTRACTObjective. This study aimed to investigate the effects of physical activity and ergonomy programme (PAEIP) on employees' musculoskeletal pain. Methods. The sampling group included 120 employees met the criteria and were randomly assigned to the intervention group (N = 57) and the control group (N = 63). Visual Analog Scale (VAS), Nordic Musculoskeletal Survey, Rapid Upper Limb Assessment (RULA) were used for collecting data. Results. When pre-test and post-test pain scores of intervention group were compared, the average post-test scores were significantly lower in neck, shoulder, wrist and low back regions than the pre-test scores. When the intervention and control groups' RULA score compared, in the intervention group whereas proportion of employees found in "acceptable posture" level was 0 percent in pre-test, it was 5.3 percent in the post-test, and in the same group, proportion of employees in "further investigation and change may be needed" level was 31.6% in the pre-test, this rate increased to 61.4% in the post-test. Conclusion. As a result, PAEIP has been found effective in reducing the ergonomic risks associated with upper extremities and rate or intensity of musculoskeletal pain.